MEASUREMENT OF INCLUSIVE PRODUCTION OF NEUTRAL HADRONS FROM Z-DECAYS - Acciarri, M; Adam, A; Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; et al. (1994)
We present a study of the inclusive production of π0, η, Ks0 and Λ based on 929,000 hadronic Z decays recorded with the L3 detector at LEP. The measured inclusive momentum distributions have been compared with predictions from parton shower models as well as an analytical Quantum Chromodynamics calculation. Comparing to low energy e+e- data, we find that QCD describes the energy evolution of the hadron spectrum. © 1994.